Closing the ESG Act Gap through Service-Dominant Logic and Ethical Leadership - Ilhami, Mohamad; Widyarto, Wahyu Oktri (LITPAM, 2026)
This conceptual study examines the systemic failure of ESG initiatives—the ESG Act Gap—where symbolic reporting substitutes for substantive transformation. Employing systematic conceptual synthesis of institutional theory and Service-Dominant Logic (SDL), the analysis identifies paradigmatic misalignment between Goods-Dominant Logic (GDL) and the relational nature of sustainability as the root cause of persistent decoupling. The article introduces the novel Impact Coupling framework as a process mechanism, enabled by leadership reconceptualized as the Ethical Institutional Architect—a leadership agency that aligns ESG commitments, operational practices, and realized socio-environmental value through stakeholder co-creation and co-validation. This framework carries practical implications for boards, investors, and organizational leaders: evaluating leaders' architectural capacity and the robustness of stakeholder feedback loops becomes a prerequisite for substantive ESG, replacing mere compliance auditing. The study proposes that substantive sustainability requires an ontological shift from managing firm outputs to architecting service ecosystems in which substantive impact becomes inherent to value creation. Ultimately, closing the ESG Act Gap depends on leaders' capacity to enact this SDL-based logic, transforming integrity from a reported outcome into the core process of organizing.